Diet and sociodemographic predictors of the double burden of malnutrition in urban Zimbabwe - Simbarashe Kasanzu; Joconiah Chirenda; Anesu Marume (African Journal of Primary Health Care & Family Medicine)
Background: Rapid urbanisation in low- and middle-income countries (LMICs) has intensified the double burden of malnutrition, where undernutrition and overnutrition coexist in the same population